The Effect Used of Local Bioactivators In Citronella Waste on The Content of Dry Matter, Organic Matter, and Crude Protein - Astuti, Tri; Akbar, Syahro Ali; Basyirun, Fajri; Dani, Nofrian R (Journal of Animal Nutrition and Production Science, 2023)
This research aims to determine the effect of rumen-content bioactivators in citronella waste on dry matter, organic matter, and crude protein content. Completely Randomized Design with 5 treatments with different incubation times, namely (0, 5, 10, 15, and 20 days), each treatment was repeated three times. The variables observed in this study were dry matter content, organic matter, and crude protein. This study showed that the length fermentation of citronella waste with rumen content bioactivator had no significant effect (P>0.01) on dry matter. On organic matter and crude protein, fermentation of citronella waste using rumencontent bioactivators had a hight significant effect (P<0.01). Based on the research results, it can be concluded that fermenting citronella waste using a rumen content bioactivator at a dose of 10% with long incubation times (0, 5, 10, 15, and 20 days) can increase the content of crude protein and organic material in curing for 20 days.